Management of extranodal lymphoma of the spine: a study of 30 patients - Hashi, Shamsudini (CNS Oncol, 2018)
Extranodal lymphoma of the spine is often a late manifestation of systemic disease, and may result in symptoms of pain, neurologic compromise or spinal instability. Symptomatic relief is generally achieved by radiotherapy alone, but is not sufficient in addressing spinal instability. The indications for surgery remain controversial, but may be required for spinal stabilization, or refractory disease. Currently, there is a lack of studies that compare the indications and clinical outcomes of patients receiving surgical and nonsurgical management of spinal extranodal lymphoma. Medical records of 30 patients seen from March 2006 to August 2015, with histologically confirmed spinal lymphoma, were retrospectively reviewed. Demographic information, clinical factors, imaging, treatment and clinical outcomes were recorded. 19 patients were treated surgically and 11 nonsurgically (i.e., chemotherapy, radiation or combination). Surgery was performed for emergent neurological deterioration, mechanical stabilization, refractoriness to medical management or to perform an open biopsy for pathological diagnosis. Among those treated surgically, significantly fewer patients could carry on normal activities (KPS <70) at baseline, compared with those treated nonsurgically. However, there were no significant differences regarding pain medication use, functional status at 1 year, or mean survival (87.6 months) between groups. Surgery for extranodal lymphoma may be required in specific cases, resulting in favorable and similar outcomes compared with nonsurgical management.